Divulgação do capital intelectual: uma revisão sistemática da literatura - Nogueira, Cátia Sofia Miranda (2021)
With the evolution of the world economy, developing and managing knowledge has become the basis for its creation. This evolution led to a new concept, the one of Intellectual Capital, also emerging a need to disclose it. Thus, the present dissertation provides an overview of the main studies on the Disclosure of Intellectual Capital through a Systematic Literature Review. The PRISMA guidelines were followed and the Journal Intellectual Capital was adopted to serve as basis to choose the articles related to Intellectual Capital Disclosure. The final sample waas comprised of 109 articles published in the Journal of Intellectual Capital. This dissertation aims to identify the main themes on Intellectual Capital Disclosure’s studies, as well as the methodologies, the suggested cues for further reserach and the adopted theories. It seeks to provide a theoretical contribution on Intellectual Capital Disclosure research and fill the literatures’ gap that exists on this subject. The Systematic Literature Review intends to provide a theoretical contribution to the literature in this area, by assesing the state of the art on Intellectual Capital Disclosure and its usefulness for the various stakeholders. Its main limitation is related with the use of only one scientific journal to conduct the Systematic Literature Review. Regarding some cues for future research, it would be interesting to analyse the impact of internal and external audits on Intellectual Capital disclosure, as well as on its influence on stakeholders and on the reliability of Intellectual Capital reports. This research should also be extendend to other journals indexed in the ISI Web of Knowledge and Scopus databases.